LATE PRESENTATION OF BOCHDALEK HERNIA WITH INTESTINAL SYMPTOMS - Burki, Tariq; Amanullah, Amir; Rehman, Atta Ur; Ali, Mian Naushad (Journal of Ayub Medical College Abbottabad, 2002)
Bochdalek hernia is a rare condition that usually presents in the neonatal age. Rarely it presents late and is usually misdiagnosed. We came across a Bochdalek hernia, which presented at the age of 15 years and was initially misdiagnosed as pulmonary tuberculosis. The case history, diagnosis and management of this condition alongwith literature review are presented here.